Transcriptomic elucidation of Dahuang-Huanglian in promoting white adipose browning in high-fat diet-induced obese rats - Zhang, Ruiyao; Zhang, Yu; Xi, Xi; Du, Pengcheng; Guo, Chao; Zhang, Yanying; Song, Bing; Xu, Xiaoyan; Ni, Zhitao; Wang, Yongfeng; Bai, Min (Frontiers in Endocrinology, 2025)
ObjectiveDahuang (Rhei Radix et Rhizoma)-Huanglian (Coptidis Rhizoma) (DHHL), has been shown to effectively treat obesity caused by dietary irregularities. Nevertheless, the fundamental process driving this phenomenon has yet to be elucidated.MethodsThe chemical constituents of DHHL were analyzed using UPLC-MS/MS. An obesity model was established in rats by high-fat diet (HFD) induction and verified accordingly. Obese rats were administered various doses of DHHL. Detect and record the metabolic indicators of rats in each group. Transcriptomic analysis was used to evaluate the influence of DHHL on gene expression in obese rats. H&E staining and transmission electron microscopy (TEM) was used to observe the morphology of adipocytes. Immunohistochemistry (IHC), fluorescent immunohistochemistry (FIHC), and Western blotting (WB) were performed to detect protein expression levels.ResultsThe chemical constituents of DHHL medicinal materials were identified and analyzed using UPLC-MS/MS. Total ion chromatograms (TIC) were acquired in both positive and negative ion modes. Pie charts were generated to illustrate the abundance distribution and quantitative proportion of different components. HFD feeding induced significant increases in body weight and FBG in rats, elevated serum triglycerides (TG) and free fatty acids (FFA) levels, and promoted hypertrophy and hyperplasia of adipose tissue, while also disrupting glucose metabolism. DHHL treatment significantly improved body weight, FBG, glucose uptake capacity, and insulin sensitivity in obese rats. It also reduced blood lipid levels and lipid accumulation in a dose-dependent manner. Transcriptomic sequencing revealed that the anti-obesity effects of DHHL were closely associated with the upregulation of thermogenesis-related gene expression. KEGG pathway enrichment analysis indicated that DHHL may exert regulatory effects through pathways such as AMPK, PPAR, and PI3K. TEM observations demonstrated that DHHL increased mitochondrial numbers within adipocytes of obese rats. Molecular analyses further showed that DHHL upregulated the expression of thermogenesis-associated proteins—including PPARγ, PRDM16, and UCP1—thereby promoting the browning of white adipose tissue (WAT). Moreover, DHHL enhanced the expression levels of AMPK, SIRT1, and PGC-1α.ConclusionsDHHL effectively ameliorates HFD-induced obesity in rats, and its therapeutic mechanism is closely associated with the activation of the AMPK/SIRT1/PGC-1α signaling pathway, which promotes the browning of WAT.